Exploración gráfica sobre las fiestas patronales de los valles andinos del norte de San Juan - Torres, Cecilia (2018)
The present work is part of the project "About the Andean territory and its social practices. A geocultural inquiry in the Valley of Iglesia, San Juan", currently under development within the research program of the Secretary of Science and Technology of the UNSJ, and is justified in the commitment to contribute to the formation of the field of knowledge related to territory and specific habitats. It works on a possible reading of reality that accounts for the different ways of inhabiting, linked to the collective festive practices -religious and popular-, and how those practices reflect the ways of inhabiting the Andean region. Specifically, it is about communicating from this perspective some of the religious events (Fiestas Patronales) that take place in the Valley of Iglesia, Province of San Juan, Argentina, around the system of the communities of Angualasto, Colangüil and Malimán.